2016
DOI: 10.1007/s12282-016-0694-3
|View full text |Cite
|
Sign up to set email alerts
|

Overview on cardiac, pulmonary and cutaneous toxicity in patients treated with adjuvant radiotherapy for breast cancer

Abstract: Conservative management of breast cancer represents the standard treatment for early disease. Breast conserving surgery associated with radiotherapy for stage I-II has been proven to be as equally effective as mastectomy in term of local control, distant disease, and overall survival. The growing minimal invasive surgical approach on the axillary region, and the new breast reconstructive techniques, will probably lead to a significant decrease of the rate of side-effects related to mastectomy. Therefore, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 85 publications
1
27
0
Order By: Relevance
“…These diverse detrimental effects are associated with polymorphisms of anthracycline metabolism enzymes, which makes tailored safety dosing possible [12,21,40,41]. Although the mechanism of cardiotoxicity in AML has not been clarified, studies in breast cancer patients whose chemotherapy regimens contain anthracycline demonstrated that the impairment of heart cells is mediated by stress protective signaling and reactive oxygen [42,43]. Notably, cardiac damage does not necessarily lead to cardiac-specific death, and thus, the mortality observed here may underestimate the cardiac damage.…”
Section: Discussionmentioning
confidence: 88%
“…These diverse detrimental effects are associated with polymorphisms of anthracycline metabolism enzymes, which makes tailored safety dosing possible [12,21,40,41]. Although the mechanism of cardiotoxicity in AML has not been clarified, studies in breast cancer patients whose chemotherapy regimens contain anthracycline demonstrated that the impairment of heart cells is mediated by stress protective signaling and reactive oxygen [42,43]. Notably, cardiac damage does not necessarily lead to cardiac-specific death, and thus, the mortality observed here may underestimate the cardiac damage.…”
Section: Discussionmentioning
confidence: 88%
“…Several risk factors such as patient characteristics, RT techniques, environmental characteristics, and simultaneous systemic treatment must be considered in radiationinduced pulmonary sequelae (37).…”
Section: Irradiation-related Side Effectsmentioning
confidence: 99%
“…Recent developments in radiotherapy such as IMRT, volumetric arc therapy (VMAT), helical tomography and image-guided radiation therapy (IGRT) have provided an improvement in the dose applied to PTV and decreased the dose of the organs at risk. The published papers on IMRT indicate more uniformity in the dose applied to PTV and less acute and delayed skin complications (37).…”
Section: Irradiation-related Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This exposure has been associated with increased risk of cardiac morbidity and mortality [3]. Darby et al .…”
Section: Purposementioning
confidence: 99%